A novel model of vibration plowing effect for longitudinal ultrasonic vibration-assisted drilling. (3rd February 2023) - Liu, Yu; Ma, Lichao; Liu, Fangyuan; Fu, Bo; Yao, Jin
Abstract: A novel model of the vibration plowing effect (VPE) is proposed for the first time to reveal hitherto not well-understood ultrasonic cutting mechanics and provide a theoretical basis for controlling the tool wear and machining quality of longitudinal ultrasonic vibration-assisted drilling (LUAD). The new model includes a condition model to judge the occurrence of the VPE on the whole flank of the drill and a volume model to calculate the vibration plowing force caused by the VPE of LUAD. For one thing, a condition model is proposed to distinguish the plowing effect of conventional machining and the VPE of LUAD by comprehensively analyzing the relationship between the clearance angle of the main cutting edge and the drill's path. For another, an analytical model of the vibration plowing volume (VPV) of LUAD is derived by integrating the plowing volume of the main cutting-edge element to improve the tool wear and machining quality. Finally, a series of comparative experiments between conventional drilling (CD) and LUAD is carried out. The validity of the proposed VPE's condition model and the VPV's analytical model is verified by the chip's micromorphology and the specific plowing force of the workpiece, respectively. The experimental results show that the fine and regular textures caused by the VPE can be observed on the chip surface and side micromorphology of LUAD. However, the coarse and irregular textures are displayed in CD, which shows that the proposed conditional model is adequate. Moreover, it is calculated by the deduced VPV's analytical model that when the ultrasonic amplitude is 3.8 and 8.3 μm, the average value of the specific plowing force of Al 6061- T 6 determined in this paper is 1.399 × 10 5 N/mm 3 and 1.274 × 10 5 N/mm 3, respectively. These results agree with the value reported in other literature, that is 1.31 × 10 5 N/mm 3, which proves the validity of the proposed model of the VPV. The validated analysis model is then used to conduct predictive analysis on the VPE and vibration plowing force of LUAD under a series of process parameters. The above research results clarify the mechanism of vibration plowing under ultrasonic action and provide a theoretical basis for controlling the tool wear and machining quality of LUAD. Graphical abstract: Unlabelled Image Highlights: A vibration plowing effect's judgment model of LUAD is proposed for the first time. An analytical model of the vibration plowing volume under ultrasonic action is established. The vibration plowing force of LUAD can be obtained by the derived VPV's model Evidence of vibration plowing effect is observed on the chip side and surface. The vibration plowing condition and volume models are general in ultrasonic cutting.